Psychosocial Practices: Methodology, Epistemology and Ethics - Novais da Mata Machado, Marília (Revista Pesquisas e Práticas Psicossociais, 2019)
This work is aimed at discussing the psychosocial practices in which intervention and research are present and articulated. These practices are questioned as to their ability to generate/build psychological and social knowledge, to formulate theories, and to create methods and apparatus for action, research, self-assessment, and regulation, without losing sight of the ethical issues involved. The work asks whether practice creates psychosocial operators, that is, whether by means of its apparatus – attentive listening, free word, non-directivity, interview, among others, often in a real-life situation – it enables one to grasp the complexity of a phenomenon and to build a conceptual framework about it. It also inquires about the scientific criteria which ensure that production. As for ethics, the study evaluates the helping relationship implicated, warns against confusing practices with mission/ministry and suggests that, when it comes to intervention-research, ethics has the same importance as theory and method. Keywords: Practices; Psychosocial operators; Production of knowledge; Ethics.